Papel de Urochloa brizantha em áreas antropizadas no Cerrado - Monteiro, Marina Morais (2019)
Invasive species are among the leading causes of global ecological degradation. When invasion occurs in hotspots, such as the Brazilian Savanna, the Cerrado biome, the aggravation of the presence of these species becomes even more worrying. In the Cerrado, african grasses, mainly of the genus Urochloa, initially introduced for livestock purposes, have become a barrier to ecological restoration in recent decades. Due to aggressive competition with native plants, these species tend to occupy the ground persistently, acting as a barrier to natural regeneration and other means of restoration of degraded areas, such as planting native trees. Therefore, the control of these exotic grasses is essential for the return and maintenance of ecological balance in degraded areas in the Cerrado. Thus, the understanding of the relationship of these grasses with soil aspects of degraded environments and the development of techniques that optimize the ecological restoration processes can act favoring the ecological succession and the barrier transposition imposed by these invasive plants. Therefore, the present work aimed to establish correlations between ground cover, soil physicochemical aspects and the environments in which it occurs, and these environments present different levels of ecological degradation with the occurrence of african grass Urochloa brizantha (Hochst. ex A. Rich.) R.D.Webster. At the same time, in one of these environments, we tested the effectiveness of using polystyrene plastic tarpaulin to fray U.brizantha in the crowning region of tree species in planting to recover degraded area. The study area (16º33'26,5''S; 49º17'25,7''W) has environments allocated in a private rural property and in a vegetation fragment adjacent to the same property, in the municipality of Goiânia, Goiás state, Brazil. Originally, the area was part of the Cerrado biome, but it is currently divided into five different land use environments: 21 ha of remaining Mata Seca, 10 ha of grass with U.brizantha (Braquiarão), 6 ha in natural regeneration process of native vegetation for 15 years, 2.5 ha of 10-month-old native tree planting and two ha of 10-year-old native tree planting. Ground cover data were collected with the assist of a 40 cm x 60 cm template, which was randomly launched 30 times in each environment. Through the template the percentage of ground occupied by U. brizantha, native regenerating species, exposed ground and litter was accounted. For soil analysis, deformed samples were collected from 0 to 20 cm for soil chemistry description and undisturbed for soil physics. For the tarpaulin test, in the 10-month-old native tree planting environment, the species with the largest number of individuals (421), Anadenanthera colubrina (Vell.) Brenan, was selected and a fragment of 1m2 polystyrene plastic tarpaulin was allocated to 30 seedlings crown region’s. The seedling survival and growth data were collected by counting the number of individuals remaining alive over time and measuring their seedlings. heights (H) and collection diameters (DC), respectively. H and DC were collected in two periods, the first, five months after planting and the second 13 months after planting. Mortality data were collected at 13 months after planting. All data were submitted to multivariate analysis, the first correlating the physical soil characteristics and the ground cover with the environments and the second correlating the survival and growth of the seedlings with the percentage of U. brizantha in the crowning region of A. colubrina seedlings with the use of plastic tarpaulin In the first analysis it was noticed that the study environments differ more due to the ground cover than the physical aspects of the soil but that the soil moisture and the hydraulic conductivity of the saturated soil are the physical properties that most differentiating the environment in natural regeneration of the others. In the second analysis, for the tarpaulin test, it was concluded that the effect of tarpaulin use on the crown region of A. colubrina seedlings was sufficient to eliminate U.brizantha from this region, not influencing the mortality and incremental rate. in H and CD of the A. colubrina and was more pronounced in the rainy season than in the dry season.